Re-Evaluating the Effects of Obesity on Cancer Immunotherapy Outcomes in Renal Cancer: What Do We Really Know? - Farag, Kristine I.; Makkouk, Amani; Norian, Lyse A. (Frontiers in Immunology, 2021)
Obesity has reached global epidemic proportions and its effects on interactions between the immune system and malignancies, particularly as related to cancer immunotherapy outcomes, have come under increasing scrutiny. Although the vast majority of pre-clinical murine studies suggest that host obesity should have detrimental effects on anti-tumor immunity and cancer immunotherapy outcomes, the opposite has been found in multiple retrospective human studies. As a result, acceptance of the “obesity paradox” paradigm, wherein obesity increases cancer risk but then improves patient outcomes, has become widespread. However, results to the contrary do exist and the biological mechanisms that promote beneficial obesity-associated outcomes remain unclear. Here, we highlight discrepancies in the literature regarding the obesity paradox for cancer immunotherapy outcomes, with a particular focus on renal cancer. We also discuss multiple factors that may impact research findings and warrant renewed research attention in future studies. We propose that specific cancer patient populations may be affected in fundamentally different ways by host obesity, leading to divergent effects on anti-tumor immunity and / or immunotherapy outcomes. Continued, thoughtful analysis of this critical issue is therefore needed to permit a more nuanced understanding of the complex effects of host obesity on cancer immunotherapy outcomes in patients with renal cancer or other malignancies.